2003
DOI: 10.1097/00000478-200301000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Lung Adenocarcinomas With a Micropapillary Pattern, a Distinct Pathologic Marker for a Significantly Poor Prognosis

Abstract: Adenocarcinomas with a micropapillary pattern (MPP), featuring small papillary tufts lacking a central fibrovascular core, are thought to have a poor prognosis. To examine whether the MPP is a predictor of prognosis, clinicopathologic characteristics of adenocarcinomas were analyzed with particular reference to survival of early-stage patients. The subjects were 344 consecutive patients (female/male ratio 163:181) for whom complete surgical resection was undertaken at the Cancer Institute Hospital, Japan, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
272
5
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 227 publications
(302 citation statements)
references
References 7 publications
23
272
5
2
Order By: Relevance
“…Micropapillary pattern is characterized by papillary structures with tufts lacking a central fibrovascular core. 12 Patients with micropapillary patternpositive lung adenocarcinomas have poor prognosis and tend to present with extensive lymph node involvement and metastatic disease, [12][13][14][15] similar to patients with micropapillary carcinomas of the breast, 23 urinary bladder, 24,25 ureter 26,27 and parotid gland. 28,29 However, little is known about the mechanisms involved in micropapillary patternassociated lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropapillary pattern is characterized by papillary structures with tufts lacking a central fibrovascular core. 12 Patients with micropapillary patternpositive lung adenocarcinomas have poor prognosis and tend to present with extensive lymph node involvement and metastatic disease, [12][13][14][15] similar to patients with micropapillary carcinomas of the breast, 23 urinary bladder, 24,25 ureter 26,27 and parotid gland. 28,29 However, little is known about the mechanisms involved in micropapillary patternassociated lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lung adenocarcinomas with a micropapillary pattern have been reported to have a worse biological behavior, and that the patients with micropapillary pattern tend to present with advanced stage including lymph node metastasis. [12][13][14][15] In the present study, we investigated whether the stromal invasion grading system correlates with prognosis including pT1 (r3.0 cm) adenocarcinomas. Furthermore, we also tested whether the stromal invasion grade 3 could be subclassified into two groups that show significantly different prognoses based on the presence and absence of micropapillary pattern.…”
mentioning
confidence: 99%
“…The micropapillary pattern was defined according to the two previous studies; 18,19 it was identified as small tufts lying in alveolar spaces or in spaces encased within thin walls of connective tissue, and the tufts had no fibrovascular core. The extent of the micropapillary pattern was subclassified as none (0% of the tumor), focal (o10%), moderate (o50%), or extensive (Z50%) based on the proportion of micropapillary pattern area in the tumors.…”
Section: Histological Examinationmentioning
confidence: 99%
“…[8][9][10][11][12] Recently, a pathological entity called the micropapillary pattern has been reported to have worse outcomes in breast, 13 colon, 14 urinary tract, 15 ovary, 16 salivary gland, 17 and lung 18,19 cancer. The micropapillary pattern in lung adenocarcinoma is characterized by small papillary tufts lying in alveolar spaces or in spaces encased by connective tissues, with the tufts having no fibrovascular core, 18,19 and it has been reported as an important factor for poor prognosis. [18][19][20][21] However, the detailed histopathobiological features of the micropapillary pattern have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation